Prevalence and Intensity of Parasitic Worms on Free-Range Chickens and Egg-Laying Chickens in Muara Badak sub-District, Kutai Kartanegara - Hariani, Nova; Simanjuntak, Imilia (Jurnal ILMU DASAR, 2021)
One of the diseases often threatens the health of free-range chickens and egg-laying chickens are worm parasites (endoparasites). Parasites can be transmitted through food, drinks and the cage environment. Sanitation is one of the preventive steps carry out by farmers to protect livestock against infection from the environment. The objective of study was to determine the prevalence and intensity of parasitic worm eggs that infect the digestive tracts of free-range chickens and egg- laying hens in Muara Badak District. Research was done by observing worm eggs in fecal samples. A total of 60 samples consisting of 30 samples of egg-laying hens in Tanjung Village and 30 samples of free-range chickens in Badak Baru Village, Muara Badak. For the sample analysis technique used 2 methods are namely the floating method and the sedimentation method. The results has showed the type of worm eggs are infected the digestive tract found in free-range chickens and egg-laying chickens had consisted of Echinostoma revolutum, Raillietina echinobothrida, Raillietina tetragona, Davainea proglotina, Amoebotaenia sphenoides, Ascaridia galli, Capillaria annulata and Trichostrongylus tenuis. The highest prevalence in free- range chickens and egg-laying chickens were found in Ascaridia galli was 53.33% and 40%. While the lowest prevalence in free-range chickens against Raillietina echinobothrida and Amoebotaenia sphenoides 3.33%. egg-laying chickens are against Echinostoma revolutum, Raillietina tetragona and Trichostrongylus tenuis 6.67%. The highest intensity in free-range chickens and against Ascaridia galli was 141 eggs/individual and in egg-laying chickens was 139 eggs/individuals. The lowest intensity in this research was found in free-range chickens against Amoebotaenia sphenoides and Raillietina echinobothrida 3 eggs/individuals and egg-laying chickens against Echinostoma revolutum 5 eggs/individuals. Keywords: Endoparasites, Prevalence, Intensity, Chicken, hen.